Problematika Pembuktian Terbalik Dalam Perkara Tindak Pidana Korupsi - Reimon Supusepa (JURNAL BELO, 2019)
Probe principle flips over at ruled Indonesia bases Undang-Undang Nomor 31 Tahun 1999 jo Undang-Undang Nomor 20 Tahun 2001 Remove criminal act of Corruptions. That law applies two probe principles, which is circumscribed upending probe (section 37 and 37A) and pure upending probe (section 12B sentences 1a). But Indonesia until now haven't applied evidence upending as one is managed in that law. Probe that is applied at Indonesia to corruption case is get negative character or up on ground beyond reasonable doubt one that gets orientation on Section rule 183 KUHAP.